Action chains, relations, and rates: A conceptual framework and mathematical model for the analysis of sport games - Nestke, A. (International Journal of Performance Analysis in Sport, 2004)
The article deals with two closely related topics: A general conceptual framework and a corresponding mathematical model for observational systems designed to support the analysis of sport games. Focussing on volleyball the framework is based on the notion of action chain and its description by parameters. The central aspect of the ensuing analysis is the search for relations among the included components of the observation. Rates are introduced to provide a quantitative measure. As an application the main constituents of AZuR are explained, a program for the analysis of setter decisions in volleyball.